2021
DOI: 10.3389/fnhum.2021.732303
|View full text |Cite
|
Sign up to set email alerts
|

Which Comes First in Sports Vision Training: The Software or the Hardware Update? Utility of Electrophysiological Measures in Monitoring Specialized Visual Training in Youth Athletes

Abstract: In the present study we combined popular methods of sports vision training (SVT) with traditional oculomotor protocols of Optometric Vision Therapy (OVT) and electrophysiological indexes of EEG and VEP activity to monitor training progress and changes in performance of youth ice hockey players without the history of concussion. We hypothesized that administration of OVT protocols before SVT training may result in larger performance improvements compared to the reverse order due to the initial strengthening of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…In consequence, the temporal integration of information during stroboscopic protocols becomes more efficient ( Wilkins & Appelbaum, 2020 ), leading to a saccadic dynamics advantage later. This finding corresponds to the study results by Poltavski, Biberdorf & Praus Poltavski (2021) , who observed that training of information processing skills based on visuomotor integration and information processing skills (visual software training) in ice hockey players, indirectly trained their oculomotor system (eye quickness variables, i.e. , near-far quickness and target capture tasks).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In consequence, the temporal integration of information during stroboscopic protocols becomes more efficient ( Wilkins & Appelbaum, 2020 ), leading to a saccadic dynamics advantage later. This finding corresponds to the study results by Poltavski, Biberdorf & Praus Poltavski (2021) , who observed that training of information processing skills based on visuomotor integration and information processing skills (visual software training) in ice hockey players, indirectly trained their oculomotor system (eye quickness variables, i.e. , near-far quickness and target capture tasks).…”
Section: Discussionsupporting
confidence: 91%
“…Previous behaviors and neurophysiological evidence ( Hülsdünker, Gunasekara & Mierau, 2021a , 2021b ) showed that visuomotor reaction times after stroboscopic protocols in young elite badminton athletes were largely associated with visual processing rather than motor processes. Similarly, Poltavski, Biberdorf & Praus Poltavski (2021) used electrophysiological indexes of EEG and visual evoked potentials to monitor visual training effects and progress in the performance of youth ice hockey players. Training-induced changes in the electrophysiological indexes reflected greater efficiency in visual information processing and cognitive resource allocation following visual training with a stroboscopic protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, a copy of the hand motor command is sent to prepare the visual cortex (feed-forward process) potentially decreasing the detection latencies 35 . Studies in athletes suggest that this type of process can be improved by training 36 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Poltavski et al (2021) , the multivariate effect of ten weeks of visual training on P100 latency and amplitude had a partial eta square (ηp 2 ) of 0.13 and 0.46, respectively. Based on these findings, the effect size for the current study was calculated as 0.38.…”
Section: Methodsmentioning
confidence: 99%
“…As such, the P100 wave reflects early visual processing ( Haxby et al, 2002 ), and this VEP waveform component has been extensively studied and is commonly used in clinical and research settings to assess visual pathway conductivity ( Leocani et al, 2018 ). In a recent study conducted by Poltavski et al (2021) , youth ice hockey players trained using a combination of sports vision training (including stroboscopic intervention), and their progress was monitored with VEP tests. The study reported a significant reduction in P100 latency and amplitude following ten weeks of visual training.…”
Section: Introductionmentioning
confidence: 99%